If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 3 = (-14) Reorder the terms: 3 + c = (-14) 3 + c = -14 Solving 3 + c = -14 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + c = -14 + -3 Combine like terms: 3 + -3 = 0 0 + c = -14 + -3 c = -14 + -3 Combine like terms: -14 + -3 = -17 c = -17 Simplifying c = -17
| (r+1)+3= | | 2(x+y+8)= | | 642=1002-n | | 2w^2-3w+14=5 | | 2(-7+m)= | | -4(x+7)= | | (3/4x)-(3/x)=(3/16) | | (-2+q)+-7= | | 0=0.5x^2-cos(x)-2 | | X^2-3x+810=0 | | 1k+47=2k+24 | | 3x+10(x+y)=110 | | .5*(5-7x)=8-1(4x+6) | | 11logx/LnX | | X/21=44 | | 72w^2-512=0 | | k^2+100-20k=0 | | -17-x=2x-1 | | 27(u+15)=918 | | 5(2y-6)-9y=-3 | | 2x=168 | | 29(v+27)=899 | | 3(-5+s)= | | 56+30g=716 | | 4Y^3-52Y+28=0 | | 4(y+3)=(y+d)4whatisd | | -865=14g+115 | | X-2.4=7.5 | | 4-6w=(.5+.5) | | 4x^3+2hxy+by^2+2gx+2fy+c=0 | | 12=20-n | | y=35-2.25x |